Career Paths of the Permanent Education Press - Richard P Phelps (Nonpartisan Education Review, 2022)
Appendix 7, The Malfunction of US Education Policy: Elite Misinformation, Disinformation, and Selfishness (2023), Rowman & Littlefield Publishers